Standardized ileal digestible (SID) isoleucine requirement of barrows (15- to 30- kg) fed low crude protein diets - Doglas Batista Lazzeri; Leandro Dalcin Castilha; Patrícia Barcellos Costa; Ricardo Vianna Nunes; Magali Soares dos Santos Pozza; Paulo Cesar Pozza (Semina: Ciências Agrárias, 2017)
This study aimed to determine the SID isoleucine (Ile) requirement of starting barrows fed low crude protein. Two experiments were carried out. Experiment 1: Ten crossbred barrows were used in order to determine the SID AA of the basal diet (treatment with the lowest SID Ile level used in the growth performance experiment), averaging 15.00 ± 0.27 kg of initial weight, individually housed in metabolic cages and allotted in a complete randomized design, with two treatments, five replicates and one animal per experimental unit. Treatments consisted of a basal (14.13% CP and 0.450% of SID Ile) and a free protein diet. Experiment 2: A performance experiment was carried out to determine the SID Ile requirement when using low crude protein diets. Forty crossbred barrows were used, averaging 15.00 ± 0.87 kg of initial weight and distributed in a randomized block design with five treatments (0.450, 0.520, 0.590, 0.660 and 0.730% of SID Ile) and two animals per experimental unit. The average daily gain (ADG) (P=0.049) and protein deposition (P=0.01) were affected by the studied SID Ile levels. The daily need of SID Ile was estimated at 5.9 g when considering 0.61% as the optimum level of SID Ile in the diet for an improved ADG and protein deposition.